Bridging the gaps: New records of Hazeus ingressus Engin, Larson & Irmak, 2018 from the Eastern Mediterranean with the first morphological description of larvae - MAVRUK, SINAN; AKBULUT, GÜRKAN; CHARGUI, TAHANI; YALIM, FATMA BANU; KALECIK, EBRUCAN; YILMAZ, ŞAKIRE SERAP; AKTAŞ, ÖZGÜR (Mediterranean Marine Science, 2024)
Hazeus ingressus Engin, Larson & Irmak, 2018, a new Indo-Pacific goby, was first discovered and described on Türkiye’s Mediterranean coasts before being detected in its native location. It may have entered the Mediterranean through the Suez Canal, as a native population was later found in the northern Red Sea. This study provides further reports of H. ingressus from İskenderun and Antalya Bay, indicating that the species is also found in the eastern and central parts of the Levant Basin. Samples were obtained from Antalya Bay on July 26, September 27, and İskenderun Bay on August 26, 2021. These reports are based on larval specimens identified through DNA barcoding, highlighting the efficacy of ichthyoplankton samplings as a valuable tool for monitoring non-indigenous fish species in the Eastern Mediterranean —an area prone to biological invasions. Observing larval stages also suggests local spawning, indicating the presence of reproducing populations. Our study provides the first morphological description of H. ingressus larvae, which may serve as a valuable reference for future studies.